Pediatric dialysis - Warady, Bradley A.; Schaefer, Franz; Fine, Richard N; Alexander, Steven R. (Springer Netherlands, 2004)
Intro -- Contents -- List of Contributors -- 1The history of dialysis therapy in children -- 2The biology of dialysis -- 3The demographics of dialysis in children -- 4Organization and management of a pediatric dialysis program -- 5Vascular access -- 6Peritoneal dialysis access in children -- 7Technical aspects of the hemodialysis procedure -- 8Technical aspects of the peritoneal dialysis procedure -- 9Prescribing and monitoring hemodialysis -- 10 Peritoneal dialysis and prescription monitoring -- 11 Initiation of maintenance renal replacement therapy in infancy -- 12 The decision to initiate dialysis in children and adolescents -- 13 Maintenance hemodialysis during infancy -- 14 Maintenance peritoneal dialysis during infancy -- 15 Achieving nutritional goals for children on dialysis -- 16 Supplemental tube feeding -- 17 Growth disturbance in chronic renal failure: Etiology and treatment -- 18 Treatment of renal bone disease -- 19 Management of renal anemia -- 20 Blood pressure management in the dialysis patient -- 21 Cardiovascular considerations of pediatric ESRD -- 22 Immune function of children on dialysis -- 23 Immunizations -- 24 Peritonitis -- 25 Non-infectious complications of peritoneal dialysis and hemodialysis -- 26 Neurological side effects of dialysis and cognitive development in children with end-stage renal disease -- 27 Psychosocial care and adherence to medical regimens -- 28 Assessing the quality of life of children on dialysis -- 29 Long-term outcome of peritoneal dialysis and hemodialysis in pediatric patients -- 30 The ethics of withholding and withdrawing dialysis in children -- 31 Urological considerations in children with end-stage renal disease -- 32 Preparing the pediatric dialysis patient for transplantation -- 33 Principles of drug administration in children receiving renal replacement therapy.